Analisis Kimia Telur Ikan Tuna Mata Besar (Thunnus obesus) dari Berbagai Tingkat Kematangan Gonad - Putri, Tri Widayati; Kamaruddin, Nurulhikmah; Khairiyah, Zul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
Bigeye tuna (Thunnus obesus) is a type of large pelagic fish belonging to the Scombriade family that can spawn repeatedly during the spawning season. Bigeye tuna eggs have several phases of gonad maturity, including gonad maturity level IV and gonad maturity level V. This study aims to determine the chemical composition and mineral composition of bigeye tuna eggs (Thunnus obesus) from two levels of gonad maturity, namely gonad maturity level IV and gonad maturity level V. The parameters analyzed were water content, ash content, protein content, fat content, iron and zinc with three repetitions for each parameter. This study was conducted from June to August 2024. Sampling was carried out at two different locations with samples in the form of bigeye tuna eggs (Thunnus obesus). The results of the study showed that bigeye tuna eggs from gonad maturity level IV had a water content of 69.94%, ash content of 4.04%, protein content of 20.43%, fat content of 0.94%, iron content of 34.42% and zinc content of 142.58%. While the gonad maturity level V had a water content of 72.01%, ash content of 3.22%, protein content of 19.82%, fat content of 1.55%, iron content of 14.83% and zinc content of 172.50%. Based on the statistical results, it showed that bigeye tuna eggs had significant differences (significantly different) in water content, ash content, protein, fat, iron and zinc at two gonad maturity levels IV and gonad maturity level V.